ANALYSIS OF THE PREVALENCE, STRUCTURE AND CLINICAL CHARACTERISTICS OF DENTAL DISEASES IN MILITARY PERSONNEL SERVING IN EXTREME CLIMATIC CONDITIONS. (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
Abstract. Inflammatory periodontal diseases are considered major dental diseases, as they have been the most common among other maxillofacial disorders for many decades. The primary goal of treating inflammatory periodontal diseases is to eliminate pathogens and eliminate the negative consequences of their impact on periodontal tissue, as pathological changes in periodontal tissue occur when microorganisms are activated against the background of decreased body resistance.